Electrodeposited copper – tin coatings as catalysts for electrolysis of water in alkaline solutions - Galuza, Maryia G.; Vorobyova, Tatsiana N. (Journal of the Belarusian State University. Chemistry, 2024)
Еthylene glycol electrolyte is proposed for Cu − Sn coatings deposition on steel electrodes with nickel sublayer. The coatings contain 70 wt. % of copper and include crystalline phases of copper, tin, intermetallic Cu6Sn5, electronic type solid solution based on Cu5Sn compound, and also copper(II) and tin(IV) oxides in trace quantities. Changes in the elemental and phase composition of the coatings were determined as a result of their heating at 250 and 400 °C and leaching in 7.5 mol/dm3 NaOH solution. It has been shown that coatings heated at 400 °C exhibit electrocatalytic activity in the process of electrolytic evolution of both hydrogen and oxygen during alkaline electrolysis of water, which exceeds the activity of nickel sublayer used. These same coatings are characterised by corrosion resistance in 0.1 mol/dm3 KOH solution, which, judging by the corrosion currents, exceeds the corrosion resistance of the nickel-plated steel electrode.
Keywords: electrodeposition; Cu – Sn alloy; Cu – Sn coatings; alkaline water electrolysis; electrocatalysis; electrodes